Math-Elearning@Cat: Key Factors in the Use of Information Technologies in Secondary Mathematical Education [Math-Elearning@Cat: Factores Claves del Uso de Las Tic en Educación Matemática Secundaria] - Perez-Bonilla, A (Comite Latinoamericano de Matematica Educativa, 2016)
This article presents the main results obtained during the development of the research project Math-Elearning@cat, contextualized in secondary education. The main purpose of this research is to identify those factors which in the opinion of teachers are more relevant when it comes to mainstream Information Technologies and Communication Technologies (ICT) in mathematical subjects. This is a hybrid study, and it is based on a survey of mathematics teachers in secondary education in Catalonia (Spain).To analyze the data obtained, we used factor analysis techniques. The analysis shows that there are four factors involved in a relevant way of ICT use in mathematics classrooms. Another result of the study is the finding that teachers have, in general, a positive predisposition to the use of ICT in their teaching, although this theoretical predisposition does not seem to correspond to actual use. © 2016, Comite Latinoamericano de Matematica Educativa. All rights reserved.
Keywords: E-learning; Factor analysis; Information technology and communication technology (ICT); Mathematics education; Secondary education